2008
DOI: 10.3141/2082-15
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Travel Behavior of Elderly Women in Rural and Small Urban North Dakota

Abstract: Many studies focus on the mobility patterns of elderly people. However, few studies have explored the mobility of elderly women in rural and small urban areas. Compared with their peers in large urban areas, these women tend to face greater challenges because of limited services and mobility options. Using data from 1,021 respondents to a survey conducted in North Dakota, this study examines the determinants of the travel behavior of elderly women. In particular, a multilevel conceptual ecological model was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…The mobility of older people in rural areas in some of the same parts of the world has been studied (e.g. Hough et al, 2008;Ziegler and Schwanen, forthcoming) but has attracted less attention. Very little is known about older people outside the Western world.…”
Section: Contextualitymentioning
confidence: 98%
“…The mobility of older people in rural areas in some of the same parts of the world has been studied (e.g. Hough et al, 2008;Ziegler and Schwanen, forthcoming) but has attracted less attention. Very little is known about older people outside the Western world.…”
Section: Contextualitymentioning
confidence: 98%
“…As a result, this framework has been a key foundation for several studies analysing older people's mobility (e.g. Hough et al, 2008;Winters et al, 2015). Correspondingly, using previous literature, Mercado and Newbold (2009) summarised the key determinants of mode choice in later life as being age, gender, mobility tools, health, social issues and other factors such as financial status, education level and urban structure.…”
Section: Determinants Of Mode Choice For Older Peoplementioning
confidence: 99%
“…Böcker et al, 2016;Li et al, 2012). Older women tend to rely more on their husbands to drive them so the loss of spouse usually limits their mobility (Hough et al, 2008). Such loss is a key determinant for social isolation if alternatives, namely access to a car as passengers and public transport systems are not available (Hensher, 2007).…”
Section: Determinants Of Mode Choice For Older Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…In its Special Report 277, the TRB Committee to Review the Bureau of Transportation Statistics' (BTS) Survey Programs found that while these national surveys were useful, the surveys did not meet the needs of all users, in particular, at a local level. Hough (2007) argued ''the studies that have been conducted using NHTS data do not adequately address the travel behaviors of the rural states''.…”
Section: Introductionmentioning
confidence: 99%